Multimodality treatment of hepatocellular carcinoma: How field practice complies with international recommendations. (15th July 2018) - Sangiovanni, Angelo; Triolo, Michela; Iavarone, Massimo; Forzenigo, Laura V.; Nicolini, Antonio; Rossi, Giorgio; La Mura, Vincenzo; Colombo, Massimo; Lampertico, Pietro
Abstract: Background: Management of hepatocellular carcinoma (HCC) is framed within standardized protocols released by Scientific Societies, whose applicability and efficacy in field practice need refining. Aim: We evaluated the applicability and effectiveness of guidelines for the treatment of HCC of the American Association for the Study of the Liver (AASLD). Methods: 370 consecutive cirrhotic patients with de novo HCC in different stages, 253 BCLC A, 66 BCLC B, 51 BCLC C received treatment through a multidisciplinary team (MDT) decision and were followed until death or end of follow‐up. Results: Treatment was adherent to AASLD recommendations in 205 (81%) BCLC A patients, 36 (54%) BCLC B, and 27 (53%) BCLC C. Radiological complete response was achieved in 165 (45%) patients after the first‐line treatment, in 22 (19%) after a second‐line and in 9 (23%) after a third‐line treatment. Adherence to AASLD recommendation allowed a lower yearly mean mortality rate in BCLC A patients compared with other treatment (5.0% vs 10.4% P = .004), whereas upward treatment stage migration compared with the standard of care was associated with reduced yearly mortality in BCLC B (8.6% vs 20.7%, P = .029) and BCLC C (42.6% vs 59.0%, P = .04) patients. Conclusions: HCC multimodality treatment including other than first‐line therapy is common in clinical practice and impact on the achievement of complete response. Personalized treatment was able to provide survival benefits to patients whose profile is not accounted for by international recommendations, which need to be amended. Abstract : See Editorial on Page1550